Pemberdayaan Ibu Rumah Tangga dalam Upaya Meningkatkan Ekonomi Keluarga Melalui Pelatihan Kewirausahaan di Kelurahan Siranindi - Fajar Dakhilulloh; Budiman Sombol; Aisyah Zahratunnisa; Diva Khaerunnisa; Isna Nur Hidayati; Marwah Tunisa; Rani Purnamasari; Istiqama Istiqama; Nurasia Munir (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
The life of society in the modern era, the role of women is not only limited to being housewives, but also contributing to the family economy. Empowering housewives can improve welfare through entrepreneurship, one of which is by producing home-cooked food. In Siranindi Village, many housewives do not work and have enough free time. Crispy fried chicken entrepreneurship training aims to improve their skills in entrepreneurship and improve the family economy. The method used consists of three stages: preparation, implementation, and evaluation. The findings show that participants are enthusiastic and able to follow each step of production well. The evaluation shows that participants' skills in making crispy fried chicken have increased after participating in entrepreneurship training. This training is expected to be a solution in empowering housewives in Siranindi Village to improve their family economy.